1996
DOI: 10.1046/j.1525-1438.1996.06040333.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental site trophoblastic tumor presenting with scalp metastases

Abstract: Hartenbach EM, Saltzman AK, Zachary CB, Osborne JL, Okagaki T, Twiggs LB. Placental site trophoblastic tumor presenting with scalp metastases. Int J Gynecol Cancer 1996; 6: 333-336.Placental site trophoblastic tumor (PSTT) usually presents with vaginal bleeding or amenorrhea and an enlarged uterus. Metastasis to the skin as the presenting sign, or as a metastatic site, has not been previously reported with PSTT. We report a case of PSTT in which the presenting sign was scalp metastases and the only other disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The most common metastatic sites for GTD are the lungs, liver, and brain. Gestational trophoblastic Dermatology Online Journal || Case Presentation disease with skin metastases has been reported but is exceedingly rare [17,18]. It is reported that ETT can metastasize to the lung as well as to the brain, liver, abdominal cavity, vagina, tonsil, and lymph nodes [6,8].…”
Section: Case Discussionmentioning
confidence: 99%
“…The most common metastatic sites for GTD are the lungs, liver, and brain. Gestational trophoblastic Dermatology Online Journal || Case Presentation disease with skin metastases has been reported but is exceedingly rare [17,18]. It is reported that ETT can metastasize to the lung as well as to the brain, liver, abdominal cavity, vagina, tonsil, and lymph nodes [6,8].…”
Section: Case Discussionmentioning
confidence: 99%
“…Previous reports of skin metastases with this condition describe reddish nodules similar to those seen in our patient. 2 This is a case of a rare complication of a rare disease. It highlights some interesting symptom control issues.…”
Section: Commentmentioning
confidence: 97%
“…1 Metastases to the skin are extremely rare indeed. 2 Previous reports document only seven cases of gestational trophoblastic disease with skin metastases. 3 I present a case of a young woman with florid skin metastases that were painful and difficult to manage.…”
Section: Gestational Trophoblastic Disease With Painful Skin Metastasesmentioning
confidence: 99%
See 1 more Smart Citation